Penerapan potensi lokal dalam Pembelajaran IPA di Sekolah Menengah Pertama - Lestari, Wiwit Yuli; Rahmita, Rahmita (Jurnal Kajian Pendidikan IPA, 2025)
This study aims to analyze the implementation of local potential as a contextual approach in science learning. This research uses a qualitative approach with data collection techniques in the form of literature reviews from various scientific sources and educational policies. The review results show that local potentials, such as school gardens, home industries, and the surrounding natural environment, are utilized to teach science concepts such as ecosystems, matter and its changes, energy, environmental pollution, and other science topics. Learning strategies that can be applied include project-based learning, field visits, and direct observation, which align with the principles of the Merdeka Curriculum and the scientific approach. This implementation increases student enthusiasm, active engagement, and stronger conceptual understanding. On the other hand, there are obstacles such as limited resources to support major science concepts, the unavailability of modules based on local potential, and the lack of teacher training on local potential. The teacher's role as a learning innovator is key in packaging local potential into relevant teaching materials. Positive impacts are also seen in the strengthening of Pancasila Student Profile values, such as mutual cooperation, environmental awareness, and appreciation of local culture. This study recommends strengthening teacher capacity, policy support, and the provision of contextual learning resources to optimize the integration of local potential in science learning. Keywords: local potential, science learning, Merdeka Curriculum, Pancasila Student Profile